To Problem Pertaining to Calculation of Resistance to Heat Transfer in Modern Structures of Building External Walls - L. V. Nesterov; A. B. Kroutiline (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents a new methodology for determination of resistance to heat transfer of building external walls with the introduction of heat engineering uniformity factors obtained on the basis of calculating two- and three-dimensional temperature pattern. The methodology makes it possible to take into account influence of joints, connections with adjoining structures and jambs of external walls.